Beta-2 Agonists in sport: are the anti-doping rules meeting the needs of asthmatic athletes? - Naranjo Orellana, J.; Carranza Marquez, M. D. (British Journal of Sports Medicine, 2011)
Objectives: (a) To review the methacholine tests performed in our laboratory up until 2008; (b) to compare them with previously reported data in 2006 and (c) to examine if the anti-doping rules are meeting the needs of asthmatic athletes who really need bronchodilator treatment.